Influence of the treatment with the antineoplastic agents 5-fluorouracil and cisplatin on the severity of experimental periodontitis in rats - Novaes, Vivian Cristina Noronha [UNESP]; Ervolino, Edilson [UNESP]; Fernandes, Giovani Lopes [UNESP]; Cunha, Clara Possarle [UNESP]; Theodoro, Letícia Helena [UNESP]; Garcia, Valdir Gouveia [UNESP]; Almeida, Juliano Milanezi de [UNESP] (Springer Nature, 2022)
Purpose: The determination on how antineoplastic agents interfere on the progression of periodontitis is critical for improvement and even development of novel therapeutic approaches for periodontal management. This study evaluated the influence of chemotherapy with 5-fluorouracil (5-FU) or cisplatin (CIS) on healthy periodontal tissues and on the progression of experimental periodontitis (EP). Methods: One hundred forty-four male rats were divided into six groups (n = 24). Each group was treated with physiological saline solution (PSS) 0.9%, 5-FU, or CIS. Experimental periodontitis (EP) was induced by ligature placement. Animals were euthanized at 7, 15, and 30 days after treatment. Data were statistically analyzed (p ≤ 0.05). Results: The groups with EP and treated with 5-FU or CIS showed lower percentage of bone volume in the furcation region and higher percentage of alveolar bone loss, higher number of TRAP-positive cells, and lower number of PCNA-positive cells when compared group with EP and treated with PSS (p ≤ 0.05). Groups with EP and treated with 5-FU or CIS showed high immunolabelling pattern of RANKL, TNF-α, and IL-1β, moderate of BAX, and low of HIF-1α. Histological analysis showed severe tissue breakdown in the groups with EP and treated with 5-FU or CIS. Conclusions: Chemotherapy with antineoplastic agents 5-FU and CIS increased the intensity and duration of the inflammation and compromised tissue repair by reduction in cellular and vascular turnover. The more severe periodontal breakdown was caused by 5-FU.
Keywords: Alveolar bone loss; Antineoplastic agents; Cisplatin; Fluorouracil; Periodontitis